Optimal control of solar-powered electric bus networks with improved renewable energy on-site consumption and reduced grid dependence. (1st October 2022) - Ren, Haoshan; Ma, Zhenjun; Fai Norman Tse, Chung; Sun, Yongjun
Highlights: Optimal charging control for solar-powered electric bus networks was proposed. MILP was adopted to tackle the complex and high-dimensional charging problem. It can improve solar energy on-site consumption and reduce grid dependence. It can satisfy the complex and various constraints. It can assist in developing effective solar-powered electric bus networks. Abstract: Developing solar-powered electric bus networks in high-density cities can greatly mitigate their increasing energy and environmental challenges such as carbon emission, street-level air pollution, and renewable penetration to the power grid. However, such solar-powered electric bus networks face a charging control issue that is caused by the severe and frequent mismatch between PV power generation and bus charging demand. Without proper consideration of this mismatch, renewable energy generation cannot be effectively utilized, and heavy grid dependence (i.e., energy exports/imports to/from power grids as solar power surplus/insufficient) will still exist. Meanwhile, the electric bus network charging issue is a complex constraint-based and high-dimensional control problem that requires holistically coordinating charging operations of a large number of electric buses (i.e., when and at which terminus to charge) while satisfying various constraints (e.g., bus schedule, bus battery capacity and charging power limits, limited charging stations in a terminus). Existing charging control methods of solar-powered electric vehicles may not be applicable for this problem. To address this knowledge gap, this study proposed a mixed-integer-linear-programming-based control strategy for solar-powered electric bus networks with improved renewable energy on-site consumption and reduced grid dependence. A case study of a bus network with reference to 10 real bus terminuses in Hong Kong was used to validate the performance of the proposed control in comparison to a rule-based one (i.e., first-come-first-served [FCFS]). The results showed that the proposed control can significantly improve the renewable energy on-site consumption ratio from 0.457 to 0.813, while the grid dependence indicator was reduced from 0.809 to 0.451. The in-depth analysis showed that the proposed control can realize both temporal and spatial demand shifting which mainly contributes to the performance improvements. The results also revealed to achieve the same performance of the proposed control, the FCFS control requires installing a large-sized battery storage system, i.e., 45-MWh. The proposed control can be used to facilitate the development of solar-powered electric bus networks in high-density cities, thereby alleviating associated carbon emissions and air pollution.